Medicinal plants of the southwestern part of Belgorod oblast - Zh. M. Yakhtanigova; I. V. Kulishova; A. V. Afanasyev; V. I. Sidelnikov (Новые технологии, 2023)
Monitoring the species diversity of medicinal and aromatic plants contributes to the conservation of the gene pool of natural resources and their rational use. Since ancient times, medicinal plants have been the only source of medicinal raw materials. Despite the intensive development of chemical synthesis, plant resources are in great demand both in the pharmaceutical industry and in the national economy. They serve as a raw material for the production of medicines, pharmaceutical substances, cosmetics and biologically active additives. They are also sources of biologically active substances, objects of introduction and stimulus for the development of medicinal plant breeding and import substitution of drugs of natural origin. The need for medicinal raw materials of plant origin is constantly increasing. Separately, it should be noted that some medicinal and aromatic plants cannot be cultivated due to their biological characteristics. Meeting the needs of the country's population and the needs of the pharmaceutical industry is an important strategic issue. The Belgorod branch of the All-Russian Institute of medicinal and aromatic plants carries out many years of research, which made it possible to carry out ecological and phytocenotic evaluation of the natural plant community and analyze it on the basis of species systematics, to identify the natural potential of the local flora with selection of the most promising species for cultivation under regulated conditions. The raw material base of medicinal and aromatic plants in Belgorod region consists of a fund of raw materials harvested from wild-growing plants and a fund of raw materials collected at the expense of cultivated medicinal plants. Medicinal plants are harvested not only for the pharmaceutical industry and direct sale through pharmacies, but also for the needs of the population.